A novel ratiometric fluorescent aptasensor accurately detects patulin contamination in fruits and fruits products - Jiankang Deng (Elsevier, 2022)
Patulin (PAT) contamination in fruit and fruit products is a significant public health concern. Here, we developed a ratiometric fluorescent aptasensor for PAT detection based on aptamer-recognition and Exonuclease III amplification. Two structure selective dyes, SYBR Green I (SGI) and N-methyl mesoporphyrin IX (NMM), were used as fluorescent probes. In the developed biosensing system, the binding of PAT to aptamer triggered the liberation of cDNA. Subsequently, amplification was mediated by Exonuclease III. S1 was released from the S1-S2 duplex by enzymatic hydrolyzation and incorporated into a stable G-quadruplex. As a result, the fluorescence of SGI decreased, whereas that of NMM increased. There was a strong linear correlation between the relative fluorescence intensity and PAT concentrations (20 to 500 ng·L−1 range) (R2 = 0.99). The biosensing system was highly sensitive, and could detect PAT concentration as low as 4.7 ng·L−1. The sensor was also highly specific, and could differentiate PAT from several other related mycotoxins. In summary, we developed a new bioassay for the accurate detection of PAT contamination in fruits and fruit products. This research provides a new approach for developing ratiometric bioassays based on structure-selective dyes and enzymatic conversion processes.